On Ethnic Jokes in Indonesia - I Dewa Putu Wijana (Journal of Language and Literature, 2015)
This paper aims to describe various scripts opposed in ethnic jokes found among diverse ethnic groups in Indonesia. By examining carefully the humorous discourses extracted from humor collection, English lesson, linguistics text books, and jocular discourses ever heard as well, it is found that several scripts which are often opposed by the joking creators are language distortion, dumbness, stinginess and deceitfulness, and cunningness script. Ethnic jokes found amid various Indonesian ethnic groups essentially constitute a wealthy source to promote a harmonious multicultural society in Indonesia